Моделирование низкочастотных соединителей для применения в высокочастотных цепях - Efimenko, A. A.; Shatalov, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The paper examines the specifics of using low-frequency connectors in high-frequency circuits, taking into account the effects of crosstalk and impedance matching.